2003
DOI: 10.3171/jns.2003.99.5.0848
|View full text |Cite
|
Sign up to set email alerts
|

Sex steroid hormone exposures and risk for meningioma

Abstract: The risk for meningiomas was increased among women exposed to either endogenous or exogenous sex hormones. An unexpected relationship with increasing age at menarche was also noted; this remains unexplained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
124
5
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 141 publications
(146 citation statements)
references
References 39 publications
13
124
5
4
Order By: Relevance
“…In contrast to the Women's Health Study, no association was observed with increasing age at menarche. 13 Similar to findings in breast cancer studies, menopause appeared to be an effect modifier. The pregnancy, OC use and smoking protective effects were stronger in premenopausal women.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…In contrast to the Women's Health Study, no association was observed with increasing age at menarche. 13 Similar to findings in breast cancer studies, menopause appeared to be an effect modifier. The pregnancy, OC use and smoking protective effects were stronger in premenopausal women.…”
Section: Discussionsupporting
confidence: 66%
“…11 Studies reporting data on parity or pregnancy and brain tumors are few and not consistent. Several reports 13,24,25 have observed increased risks for meningioma with Ôever having been pregnantÕ: an East German study found no relationship with meningioma among women who are reproductively competent 2 and a recent United States hospital based case-control study saw no associations with number of pregnancies or livebirths. 14,26 Two case-control studies 11,12 have reported reduced odds ratios for parity and meningioma, although these estimates were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations